Relationship between heterosis, weight gain, and body measurements of Nellore and Charolais calves - Fernandes, Tiago Albandes; Cerdótes, Liliane; Vaz, Ricardo Zambarda; Restle, João; Ferreira, Otoniel Geter Lauz (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to assess the effect of genetic group and heterosis on the relationship between body weight and morphometric measurements, in purebred and crossbred animals from the second (G2) and third (G3) generations of Nellore and Charolais calves. Body weight (BW), average daily weight gain (ADG), foreleg circumference (FC), thoracic girth (TG), body length (BL), and croup height (CH) were measured at birth and at 63, 210, and 365 days of age in animals from G2 and G3. Charolais animals were superior to Nellore ones for gains BW, ADG, BL, and TG, as well as for the ratio between BW gain and CH gain; Nellore animals were superior for CH gains. Crossbred animals of both generations were superior to the purebred animals for gains of BW, BL, and CH. In G2, the predominance of Charolais genes resulted in greater gains of BW, ADG, FC, and TG. The G3 animals were superior to the purebred animals for ADG, FC, and TG. No differences were found for the ratio between gains of weight and morphometric measurements. Heterosis and complementarity are apparent for weight and body measurements of crossbred calves from rotational crossings.